Revision of the bee subgenus Centris (Wagenknechtia) Moure, 1950 (Hymenoptera: Apidae: Centridini) - Vivallo, Felipe (Zootaxa, 2013)
In this paper, a complete taxonomic revision of the species of Centris (Wagenknechtia) Moure is presented for the first time. The following species are recognized: Centris cineraria Smith, C. escomeli Cockerell, C. moldenkei Toro & Chiap-pa, C. muralis Burmeister, C. orellanai Ruiz, C. rhodophthalma Pérez and C. vardyorum Roig-Alsina. Floral associations, distribution records, and diagnoses of both sexes based on type specimens, are given. An identification key, illustrations, along with an updated catalogue of all species of the subgenus, are also provided. In addition, a neotype for Centris orel-lanai is designated.